X-linked neonatal-onset epileptic encephalopathy associated with a gain-of-function variant p.R660T in GRIA3 - Sun, Jia-Hui; Chen, Jiang; Ayala Valenzuela, Fernando Eduardo; Brown, Carolyn; Masser-Frye, Diane; Jones, Marilyn; Romero, Leslie Patron; Rinaldi, Berardo; Li, Wenhui Laura; Li, Qing-Qing; Wu, Dan; Gerard, Benedicte; et al. (PLoS genetics, 2021)
The X-linked GRIA3 gene encodes the GLUA3 subunit of AMPA-type glutamate receptors. Pathogenic variants in this gene were previously reported in neurodevelopmental diseases, mostly in male patients but rarely in females. Here we report a de novo pathogenic missense variant in GRIA3 (c.1979G>C; p. R660T) identified in a 1-year-old female patient with severe epilepsy and global developmental delay. When exogenously expressed in human embryonic kidney (HEK) cells, GLUA3_R660T showed slower desensitization and deactivation kinetics compared to wildtype (wt) GLUA3 receptors. Substantial non-desensitized currents were observed with the mutant but not for wt GLUA3 with prolonged exposure to glutamate. When co-expressed with GLUA2, the decay kinetics were similarly slowed in GLUA2/A3_R660T with non-desensitized steady state currents. In cultured cerebellar granule neurons, miniature excitatory postsynaptic currents (mEPSCs) were significantly slower in R660T transfected cells than those expressing wt GLUA3. When overexpressed in hippocampal CA1 neurons by in utero electroporation, the evoked EPSCs and mEPSCs were slower in neurons expressing R660T mutant compared to those expressing wt GLUA3. Therefore our study provides functional evidence that a gain of function (GoF) variant in GRIA3 may cause epileptic encephalopathy and global developmental delay in a female subject by enhancing synaptic transmission.